John Henry Newman and the Existence of God - McHugh, Paul James (New blackfriars, 2026)
Regarding proofs for the existence of God, two things are well known of St John Henry Newman. First, he was chary about aspects of the Christian Evidences, a great accumulation of Christian apologetics in which Paley’s writings occupied a central place. Second, that he favoured an argument from conscience as ‘a proof common to all, to high and low’. This paper examines what might have been behind Newman’s convictions. It argues that metaphysical and epistemological emphases of early modern philosophy had semantic repercussions for ‘standard’ apologetics such as St Thomas’ Five Ways. In a new social imaginary, they suffer distortion and lose vitality as they begin to be reprogrammed to operate according to modern epistemological canons. Similarly, Paleyan arguments from design as they appear in the Christian Evidences were built on an evidential standard perhaps notionally compelling but in reality false to how a person really comes to conviction about belief in God. In the end, this paper argues that there is an odd kinship between Newman’s argument from conscience and St Thomas’ Five Ways, if these latter are read in their intended medieval light rather than in a modern light.